2016
DOI: 10.1507/endocrj.ej16-0374
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine supplementation for the management of fatigue in patients with hypothyroidism on levothyroxine treatment [Letter to the Editor]

Abstract: mately 10% of hypothyroid patients, especially those with no remnant thyroid tissue (i.e., post-radioiodine, post-thyroidectomy hypothyroidism) [3]. This residual symptomatology consists essentially in physical and/or mental fatigue, and can be addressed by adding L-T3 to L-T4 [3].Within the limits of words and references permitted by the journal and not to give complete details that would preclude publication of a full paper, we would like to give some information in support of the An and colleagues' article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…In subgroups, both the physical and mental fatigue scores improved significantly in patients younger than 50 years and those with free T3 ≥ 4.0 pg/mL by treatment with l -carnitine compared with placebo. Other case-based studies have indicated a benefit from l -carnitine on hypothyroid symptoms, but all of them have been case-based [45], while other studies may support benefits in the corticosteroid hormone setting [46].…”
Section: Carnitine: Compound and Physiologymentioning
confidence: 99%
“…In subgroups, both the physical and mental fatigue scores improved significantly in patients younger than 50 years and those with free T3 ≥ 4.0 pg/mL by treatment with l -carnitine compared with placebo. Other case-based studies have indicated a benefit from l -carnitine on hypothyroid symptoms, but all of them have been case-based [45], while other studies may support benefits in the corticosteroid hormone setting [46].…”
Section: Carnitine: Compound and Physiologymentioning
confidence: 99%
“…Carnitine determines good cardiac function and a reduction in oxidative stress, inflammation, and necrosis processes. The relationship between carnitine and thyroid function comes from clinical studies showing the antagonistic thyroid hormone action effects of C0 [ 19 , 20 , 21 , 22 ] and a positive correlation between urinary carnitine with serum thyroxin concentration [ 23 ]. In our study, C0 was lower in newborns whose mothers used iodized salt during pregnancy ( Figure 2 C).…”
Section: Discussionmentioning
confidence: 99%
“…Such favorable effects of the omega-3 PUFA on consequences in the peripheral tissues that are caused by opposite states of thyroid dysfunction confer to the omega-3 PUFA a modulatory role that is reminiscent of another dietary nutrient, L-carnitine. Indeed, beneficial effects of L-carnitine were reported both in the hyperthyroidism setting ( 144 , 145 ) and in the hypothyroidism setting ( 146 , 147 ), with a modulatory role also demonstrated in the tissue glucocorticoid hormone action ( 148 ).…”
Section: Omega-3 Pufa-based Nutraceuticals In the Setting Of Thyroid ...mentioning
confidence: 99%